Central metabolite changes and activation of microglia after peripheral interleukin-2 challenge - Schneider, Peggy; Sartorius, Alexander; Spanagel, Rainer (Brain, behavior and immunity, 2012)
Interleukin (IL)-2 regulates the immune response through the proliferation of activated T-cells and also exerts effects on the central nervous system (CNS). Alongside having marked neurobehavioral effects, IL-2 has been suggested to impact on various psychiatric disorders. The immune-CNS communication of IL-2 remains unclear, although, it is suggested that microglia are the source and target of IL-2. Here, we analyzed changes in brain metabolites following a peripheral IL-2 challenge and examined the contribution of microglia in mediating these effects. Rats were assessed by magnetic resonance spectroscopy (MRS) in a 9.4T scanner for baseline metabolite levels in the prefrontal cortex (PFC) and the hippocampus. After 7days animals were scanned again following a single injection of IL-2 (2.5μg/kg) and then tested on the elevated plus-maze for the correlation of IL-2-induced brain metabolites and measures of anxiety. In another experiment CD25+ microglia cells were determined. A separate group of rats was injected either with IL-2 or vehicle, and afterward the PFC and hippocampus were dissected and fluorescence activated cell sorting (FACS) analysis was performed. The MRS scans in the intra-individual study design showed a significant increase in myo-inositol in the analyzed regions. A significant correlation of anxiety-like measures and myo-inositol, a marker for microglia activity, was found in the hippocampus. The FACS analysis showed a significant increase in CD25+ microglia in the hippocampus compared to controls. The results support the role of microglia as a mediator in the immune-CNS communication and the effects of peripheral IL-2.
Gesehen am 06.04.2018